Optimalisasi Peran Masjid Dalam Pembangunan Sosial Ekonomi Jamaah : (Studi Kasus Masjid Al Bayyinah Jenu Tuban) - Maziyah Mazza Basya; Sulthon Syarifudin (JCSE: Journal of Community Service and Empowerment, 2023)
The purpose of this study was to determine the optimization of the role of the mosque in the socio-economic development of the congregation of the Al Bayyinah Jenu Tuban Mosque in particular, and the surrounding community in general. Researchers collected data in the form of activities which are a form of socio-economic development of the congregation of the Al Bayyinah Jenu Tuban Mosque, as well as the problems faced by the mosque and congregation in the social economic development of the congregation of the Al Bayyinah Jenu Tuban Mosque. The research approach used in this study is a qualitative approach, which places more emphasis on observing phenomena and researching more on the substance of the meaning of these phenomena. This type of research is a case study taken from field research. The results of this study are that the Al Bayyinah Jenu Tuban Mosque has potential that has not been utilized optimally related to the socio-economic development of its congregation. The activity in the form of an economic business that is run by the Al Bayyinah Jenu Tuban Mosque is the empowerment of the congregation through the activity of one Islamic boarding school one product and canteen management activities, where a well-systemized and professional managerial management is still needed.